No more failures ten steps to equity in education - Field, Simon; Kuczera, Małgorzata (OECD, 2007)
This publication challenges the assumption that there will always be failures and dropouts, those who can't or won't make it in school. In fact, initiatives in many countries demonstrate that it is possible to successfully tackle school failure and dropout rates -- and to reduce the huge social cost of adults without basic skills. This book offers a comparative perspective on how different countries have handled equity in education. Among the issues it explores are: tracking, streaming and academic selection; school choice; secondary education structures and second chance programs; grade repetition; links between school and home; early childhood education; resource allocation; targets for equity; and the special needs of migrants and minorities. The book identifies three key areas for delivering equity in education (the design of education systems, classroom practices and resourcing) and proposes ten concrete policy measures, backed by evidence, on how to reduce school failure and dropout rates.--Publisher's description.
Keywords: Educación y Estado - Países OECD; Impartialité; Intégration scolaire; Onderwijsbeleid; Vergelijkende onderwijskunde; Voortijdig schoolverlaten; Éducation - Politique gouvernementale - Pays de l'Organisation de coopération et de développement économiques; Education and state -- OECD countries; Fairness; Inclusive education; Chancengleichheit; Integrativer Unterricht